2012
DOI: 10.2147/ijgm.s17410
|View full text |Cite
|
Sign up to set email alerts
|

Plain abdominal radiography in acute abdominal pain; past, present, and future

Abstract: Several studies have demonstrated that a diagnosis based solely on a patient’s medical history, physical examination, and laboratory tests is not reliable enough, despite the fact that these aspects are essential parts of the workup of a patient presenting with acute abdominal pain. Traditionally, imaging workup starts with abdominal radiography. However, numerous studies have demonstrated low sensitivity and accuracy for plain abdominal radiography in the evaluation of acute abdominal pain as well as various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…It has a reported sensitivity of 69-80% for bowel obstruction [12][13][14][15] but is insensitive in assessing for complications or etiology. In addition, abdominal radiographs are neither sensitive nor specific for detection of intestinal ischemia or infectious/inflammatory conditions such as diverticulitis, colitis or appendicitis.…”
Section: Imaging Techniques Radiographymentioning
confidence: 99%
“…It has a reported sensitivity of 69-80% for bowel obstruction [12][13][14][15] but is insensitive in assessing for complications or etiology. In addition, abdominal radiographs are neither sensitive nor specific for detection of intestinal ischemia or infectious/inflammatory conditions such as diverticulitis, colitis or appendicitis.…”
Section: Imaging Techniques Radiographymentioning
confidence: 99%
“…The limitations of the abdominal x ray in patients with acute abdominal pain are now widely accepted, as the greater use of ultrasound,5 and particularly CT scanning, has made its deficiencies glaringly apparent. X rays of the spine for trauma or back pain are now indicated only in specific circumstances according to recent guidance,6 replaced when necessary by CT or magnetic resonance imaging in selected patients when imaging is essential to managing their treatment.…”
mentioning
confidence: 99%
“…16 Abdominal and pelvis radiographs require approximately 0.7 mSv each. 17 The average dose for CT Abdomen/ Pelvis is between 10 and 24 mSV. 18,19 However, a recent study showed that the median effective dose for CT scan of a multiphase abdomen and pelvis is 31 mSV.…”
mentioning
confidence: 99%